Factors influencing net income from steers through feedlot - Schalles, R.R.; Zoellner, K.O.; Long, K. (Kansas State University. Agricultural Experiment Station, 2011)
Calves that gained rapidly before going into the feedlot continued to gain rapidly on feed and were more profitable to both the cow-calf operator and the feeder. When fed to their genetic potential, large frame, heavy, young cattle were worth more to the cattle industry than light calves.
Keywords: Beef; Net income; Feedlot; Steers